2004
DOI: 10.1002/nme.1101
|View full text |Cite
|
Sign up to set email alerts
|

Modelling heat transfer in two‐fluid interfacial flows

Abstract: SUMMARYThis paper presents a method to calculate heat transfer across an interface separating immiscible fluids. A volume tracking method was used to model the simultaneous movement of mass, momentum and energy across cell boundaries. Both first-and second-order methods were used to approximate temperature fields with sharp gradients that exist near the fluid-fluid interface. Temperature distributions around hot droplets surrounded by a colder fluid with uniform velocity were calculated and the magnitude of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Pericleous et al (1995) used the SEA method for modeling free-surface flows and adopted the Van Leer total-variation diminishing (TVD) scheme for the discretization of the energy equation instead of an upwinding scheme to avoid the artificial heat loss across the interface due to numerical smearing. However, the mere use of a Van Leer TVD scheme for the discretization of the scalar-transport equation does not completely eliminate the artificial diffusion of the scalar across the interface (Mehdi-Nejad et al, 2004). Most VOF methods tackle the issue of artificial numerical diffusion of the scalar across the interface by geometrically advecting the scalar concentration field in a manner consistent with the advection of the volume fraction field (Davidson and Rudman, 2002, Alke et al, 2009, Bothe and Fleckenstein, 2013, Berry et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Pericleous et al (1995) used the SEA method for modeling free-surface flows and adopted the Van Leer total-variation diminishing (TVD) scheme for the discretization of the energy equation instead of an upwinding scheme to avoid the artificial heat loss across the interface due to numerical smearing. However, the mere use of a Van Leer TVD scheme for the discretization of the scalar-transport equation does not completely eliminate the artificial diffusion of the scalar across the interface (Mehdi-Nejad et al, 2004). Most VOF methods tackle the issue of artificial numerical diffusion of the scalar across the interface by geometrically advecting the scalar concentration field in a manner consistent with the advection of the volume fraction field (Davidson and Rudman, 2002, Alke et al, 2009, Bothe and Fleckenstein, 2013, Berry et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that even at temperatures below the boiling point the temperature rise in the liquid may cause changes in thermophysical properties leading to a significant increase in the spreading ratio, indicating that neglecting the heat transfer in the spreading stage of motion, as commonly done in modeling spray impact, may therefore lead to erroneous initial conditions for the subsequent analysis of the evaporation process. Interfacial heat transfer from multiple molten tin droplets falling in oil was numerically simulated in (Mehdi-Nejad et al, 2004, 2005 using a VOF-based computational model. Results showed a considerable change in the temperature distribution of the upstream droplet due to heat dissipation from the downstream droplet.…”
Section: Introductionmentioning
confidence: 99%
“…In interface tracking methods (front tracking [9,10] and immersed boundary [11,12]), Lagrangian particles are used to track the interface and are advected by the velocity field. In interface capturing methods (volume of fluid [VOF] [11,13,14], level set [15][16][17][18], and phase field [19][20][21][22]), the interface is implicitly captured by a contour of a particular scalar function. Many numerical techniques, including immersed boundary [23][24][25][26][27][28][29][30], VOF [31][32][33][34][35][36][37][38][39][40], and level set [41][42][43][44][45][46][47][48], use the concept of a regularized Dirac delta function to account for interfacial effects (this is described in more detail in Section 2), and many previous studies show that an appropriate delta function is required to obtain more accurate results.…”
Section: Introductionmentioning
confidence: 99%